Refugee and Asylum News Coverage in UK Print and Online Media. (25th January 2020) - Blumell, Lindsey E.; Bunce, Mel; Cooper, Glenda; McDowell, Christopher
ABSTRACT: The representation of asylum is important, yet there is little research of how this topic is reported online. This article addresses this gap through a study of UK print and online media ( N  = 2018). Articles were examined for their soft and hard news focus. Results show both partisanship and the medium play an important role. Online news covered more soft and hard news topics regardless of partisanship. However, examining the focus and style, right-leaning print and online publications focused more on criminality, while left-leaning publications focused on victimisation. These findings question the received wisdom that partisanship is the most significant variable shaping when reporting asylum. We purport that both the medium and partisanship are important to consider.